Ambivalensi Sikap di balik Kebijakan Desain di Indonesia - Triharini, Meirina; Malasan, Prananda Luffiansyah; Puspita, Arianti Ayu; Taepoer, Raditya Ardianto (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
Design intervention in the craft sector is one of the issues that continues to grow in design studies. Ranging from the studies on the co-design process between the designers and crafters to the focus on the wider sociocultural context that influences the craft development process. Recently in Indonesia, design interventions in the craft sector are often carried out under the government policies or initiatives to bring designers and crafters to collaborate. In this study, we focus on one of Indonesia government's policies, namely Designer Dispatch Service Program, to develop craft products in various locations in Indonesia through a design approach. One of the outstanding features of this program is the instrument consists of the organizational form, timeline, and regular evaluation meetings, to control and monitor the collaboration process of designers and crafters. Using the descriptive approach to dissect the interaction between each actor and the policy instruments, we found that each actor continuously adjusts the instrument accordingly to their concern and motivation regarding the policy goals. There are also unspoken goals of each actor which are less concerned about the products being exported. Finally, this study shows that despite the top-down policy being well carried out, we found ambivalent attitudes of the actors by continuously descripting the design process which was set by the policy.